The Effect of Motivation and Job Satisfaction on Employee Performance with Organizational Citizenship Behaviour as a Mediating Variable at the Regional Research and Development Agency of East Tanjung Jabung Regency - Gustin Wahyudi; Arna Suryani Arna; Sudirman Sudirman (Dinasti Publisher, 2024)
Abstract: The purpose of this study is to find out how employee performance is affected by job satisfaction and motivation, as well as organizational citizenship behavior a mediating variable at the Regional Research and Development Agency of East Tanjung Jabung Regency. The object of research in this study is the effect of motivation and job satisfaction on employee performance with organizational citizenship behavior as a mediating variable at the Regional Research and Development Agency of East Tanjung Jabung Regency. The methods used in this research are descriptive verification and quantitative methods. Based on the approach, it can be seen that the number of samples is 65 people. This study utilizes the way examination technique. According to the findings of the study, both job satisfaction and motivation at work have a significant impact on organizational citizenship behavior (OCB). Furthermore, work motivation and job satisfaction partially have a significant effect on organizational citizenship behavior (OCB). Work motivation and Job Satisfaction simultaneously have a significant effect on Performance. Furthermore, work motivation and job satisfaction partially have a significant effect on performance. Organizational citizenship behavior (OCB) partially has a significant effect on employee performance at Balitbangda East Tanjung Jabung Regency.